Finding Minimal Optimal Indent Separation for Polystyrene via Instrumental Nanoindentation and FEA Method - Chulin Jiang; Michael Davis; Jurgita Zekonyte (Applied Sciences, 2020)
Nanoindentation became a standard non-destructive technique to measure mechanical properties at the submicron scale of various materials. A set of empirical rules were established to guarantee the validity of the results. One of those rules is the separation between individual indents that should be 20–30 times maximum indentation depth. This paper investigates the influence of the distance between indents on the accuracy of mechanical properties for polystyrene with a view to determine minimum optimal separation that is needed to measure various material properties. A series of different depths with three different orientations was considered through both the experimental and finite element method to explore the relationship between the distance and indentation depth. Both methods demonstrated that hardness and modulus values for polystyrene keep stable with the distance approximately 15 times the maximum indentation depth for the matrix type set up, and nominal separation of 10 is enough when indents are executed in a single row or column.